The principal's guide to curriculum leadership - Sorenson, Richard D; Goldsmith, Lloyd Milton; Méndez, Zulma Y.; Maxwell, Karen Taylor (Corwin Press, 2011)
This guide walks headteachers through the curriculum development and renewal process with a focus on integrating standards. Includes case studies, activities, and curriculum models.